Benchmarking: the five year outcome of rheumatoid arthritis assessed using a pain score, the Health Assessment Questionnaire, and the Short Form-36 (SF-36) in a community and a clinic based sample. Issue 10 (1st October 2001) - Wiles, N J; Scott, D G I; Barrett, E M; Merry, P; Arie, E; Gaffney, K; Silman, A J; Symmons, D P M
Abstract : BACKGROUND: Treatment, and therefore outcome, of rheumatoid arthritis (RA) will improve in the next few years. However, improvement in outcome can only be judged against the probability of certain outcomes with current conventional treatment. AIM: To document the five year outcome of RA in the late 1990s. SETTING: Norfolk Arthritis Register (NOAR). DESIGN: Longitudinal observational cohort study. METHODS: 318 patients with recent onset inflammatory polyarthritis recruited by NOAR in 1990–91 completed five years of follow up. Four groups were assessed: the whole cohort, all those referred to hospital, those who satisfied criteria for RA at baseline, and those referred to hospital who satisfied criteria for RA at baseline. Outcome was assessed with a visual analogue scale for pain, the Health Assessment Questionnaire (HAQ), and the Short Form-36 (SF-36). RESULTS: Of the RA hospital attenders, 50% had a visual analogue scale pain score of 5 cm or less and an HAQ score of 1.125 or less. SF-36 scores were reduced in all domains. Results are presented as cumulative percentages. CONCLUSIONS: These results can be used for comparison and to set targets for improvement.